Spontaneous remission of fully symptomatic visceral leishmaniasis. Issue 1 (December 2015) - Mouri, Oussama; Benhamou, Mathilde; Leroux, Gaëlle; Chartrel, Nathalie; Devidas, Alain; Thellier, Marc; Amoura, Zahir; Costedoat-Chalumeau, Nathalie; Buffet, Pierre
Abstract Background Visceral leishmaniasis (VL), i.e., infection withLeishmania sp. associated with high fever, weight loss, massive splenomegaly and markedly altered laboratory parameters, is generally fatal if untreated. The possibility of transient spontaneous remission of fully symptomatic visceral leishmaniasis (VL) has been mentioned but, to our knowledge) has never been documented. Case presentation We report the first documented history of a patient with overt, confirmed VL experiencing a complete remission in the absence of any anti-leishmanial therapy. The diagnosis of VL at the time of the self-resolving episode was strongly suspected based on clinical presentation and presence of antileishmanial antibody, then unequivocally confirmed years later by the presence of an amastigote on a stored smear and the positive quantitative PCR withLeishmania -specific primers from the material scraped from this same slide Conclusion This report demonstrates that complete spontaneous remission may occur in patients with overt, fully symptomatic VL. VL should therefore be considered in cases of self-resolving or relapsing episodes of fever of unknown origin. Confirmation should be based on both serological tests and specific PCR on a blood sample.